Damage index in childhood-onset systemic lupus erythematosus in Egypt - Salah Samia; Lotfy Hala M; Mokbel Abir N; Kaddah Ahmed M; Fahmy Nouran (BMC, 2011)
Abstract Background To investigate the prevalence of cumulative organ damage among Egyptian children with juvenile-onset systemic lupus erythematosus (jSLE) and the relationships between the organ damage and the demographic data, clinical variables, and disease activity. Methods A total of 148 patients with jSLE have been followed in the pediatric rheumatology clinic and section at Cairo University. These patients were evaluated by retrospective chart review. The organ system damage due to SLE was measured using the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI). Risk factors for damage were also studied including demographic criteria as well as clinical and laboratory manifestations. Results Overall, 43.9% of the patients had damage within a mean of 6.57 ± 3.59 years of disease diagnosis. Neuropsychiatric (NPS-21%) and renal (16.9%) system involvement were observed most frequently, followed by cardiovascular (11.5%), skin (9.5%), pulmonary (6.1%), and ocular (4.8%), with a mean SDI score of 0.93 ± 1.37. In our study, the presence of neuropsychiatric manifestations at diagnosis showed the strongest association with the presence of later disease damage. The number of SLE diagnostic criteria at presentation was strongly associated with the total SDI score, and the renal damage was significantly more prevalent in patients with age at disease diagnosis below 10 years of age. A higher mean disease duration was found in patients with musculoskeletal damage. Conclusion We found that cumulative organ damage, as measured by the SDI, was present in 43.9% of Egyptian patients with juvenile-onset SLE. The damage was significantly more likely in patients who had more SLE diagnostic criteria at time of disease presentation and NPS manifestations at the time of diagnosis.